STRUCTURAL AND IMMUNOHISTOCHEMICAL FEATURES OF THE NORMAL BRAIN AND THEIR MODULATION BY EXTERNAL FACTORS. - Hamidova Guli Komilovna (TADQIQOTLAR, 2025)
Abstract This article provides a scientific analysis of the normative morphological and immunohistochemical features of the brain, as well as the factors that influence them. The normal structure of brain tissue, the distinctive morphological characteristics of neurons and glial cells, the importance of the blood–brain barrier, and their role in overall body functioning are thoroughly discussed. The article also examines the possibilities of assessing the physiological state of the brain using immunohistochemical methods that identify markers, proteins, and neurotransmitter systems. The influence of external and internal factors (genetic predisposition, toxic effects, inflammatory processes, stress, and environmental conditions) on brain morphology and immunohistochemical indicators is analyzed based on scientific literature. The results of this research serve as an important theoretical and practical foundation for the early diagnosis and prevention of neurological diseases, as well as for the development of neuroprotective therapies.